2021
DOI: 10.1111/jocn.16082
|View full text |Cite
|
Sign up to set email alerts
|

The effect of family‐based intervention for adults with diabetes on HbA1c and other health‐related outcomes: Systematic review and meta‐analysis

Abstract: Aims and objectives To evaluate the effectiveness of family‐based intervention for adults with diabetes on glycosylated haemoglobin and other health‐related outcomes. Background The impact of family‐based intervention on adults with diabetes has been evaluated in various studies, but there is uncertainty about their effect on health‐related outcomes for adults with diabetes. Design A systematic review and meta‐analysis of randomised controlled trials. Methods A review was performed and reported according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 100 publications
3
8
0
Order By: Relevance
“…In a recent trial evaluating another family-focused intervention among adults with type 2 diabetes, Rosland et al [22] also found improved self-efficacy and self-care behaviors, but not HbA1c. In Zhang et al’s 2021 meta-analysis of family-based interventions for adults with diabetes, there was an overall effect on HbA1c, but the effect was much larger when the length of follow-up was 6 months or less [45]. This aligns with our study, where HbA1c trended toward significance at 6 months and then dissipated by 9 months.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a recent trial evaluating another family-focused intervention among adults with type 2 diabetes, Rosland et al [22] also found improved self-efficacy and self-care behaviors, but not HbA1c. In Zhang et al’s 2021 meta-analysis of family-based interventions for adults with diabetes, there was an overall effect on HbA1c, but the effect was much larger when the length of follow-up was 6 months or less [45]. This aligns with our study, where HbA1c trended toward significance at 6 months and then dissipated by 9 months.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggest reducing harmful involvement may be necessary to improve HbA1c; but reducing harmful involvement is challenging. Zhang et al’s [45] meta-analysis found significant improvement in helpful involvement but a non-significant improvement in harmful involvement [45]. Finally, FAMS did not improve medication adherence despite tailored and interactive texts supporting adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, screening for SDOH (e.g., loss of employment, birth of a child, or other family-based stresses) should also be incorporated into routine care (342). In circumstances where individuals other than the person with diabetes are significantly involved in diabetes management (e.g., caregivers or family members), these issues should be monitored and treated by appropriate professionals (341,343,344).…”
Section: Screeningmentioning
confidence: 99%
“…This study is grounded in a CBPR approach, which engages Marshallese community members in the research process and builds on the relationship that the study team has cultivated with the Marshallese communities in Arkansas and Oklahoma. This study will add to a growing body of literature on family models of DSMES [ 65 , 66 , 80 ]. This study will provide new and innovative information on the effectiveness of F-DSMES delivered by CHWs in an FBO setting with Marshallese patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%